Legal Review of The Role and Implementation of The Obligations of Notaries in Changing The Articles of Association of Limited Liability Companies - Prasetiyo, Yon Rizeki Eko; Widayati, Widayati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to determine and analyze the role of notaries in the process of changing the articles of association of limited liability companies and to determine and analyze the legal consequences of the role of notaries in changing the articles of association of limited liability companies. The approach method in this study is the sociological legal approach method. The research specifications used are analytical descriptive research. The type of data uses primary and secondary data. The results of the research and discussion in this study are: The role of notaries in the process of changing the Articles of Association of Limited Liability Companies (PT) is very important, because notaries are responsible for ensuring that the changes are made in accordance with applicable legal provisions. Notaries play a role in preparing and witnessing the signing of the deed of change to the Articles of Association by shareholders, as well as ensuring that the necessary procedures, such as approval of the General Meeting of Shareholders (GMS), have been carried out correctly. In addition, notaries are also required to ratify the changes and register them with the Ministry of Law and Human Rights (Kemenkumham) to obtain ratification and a legal number. Thus, notaries ensure that changes to the Articles of Association of PT are valid and legally recognized. Furthermore, for the second discussion, Notaries also play a role in the process of changing the articles of association of a PT, such as: Making a notarial deed, Ensuring business capital and shares, Ensuring the company's organs, Submitting an application for approval from the Minister of Law and Human Rights, Providing legal counseling. The existence of a Notary is inseparable from the requirements stating that a Notary is someone whose data can be trusted, relied on, and whose stamp and sign provide evidence and guarantees that are of sufficient value. Based on this description, for each change to the Company's Articles of Association, a Notary must make a deed of amendment to the Articles of Association, where this deed is another deed that contains changes to the previous Articles of Association.